Stability Studies of a Tetraethyl Orthosilicate-Based Thixotropic Drug Delivery System - Emma Barrett-Catton; Elizabeth M. Arrigali; Bogdan A. Serban; Kolton C. Sandau; Monica A. Serban (Pharmaceutics)
Background/Objectives: This study assessed the effects of formulation components on the long-term stability of a previously described tetraethyl orthosilicate-based drug delivery system. Early stability studies of a product concept are crucial not only to provide information on the overall system stability and individual components’ contributions to it, but also to identify opportunities for dosage form optimization and to define its use case. Methods: We assessed the time-dependent thixogel properties—specifically, mechanical strength, thixotropy, release of model drug, and dry substance—in both real-time and accelerated shelf-life determination set-ups. Results: Our findings indicate that the concentration and molecular weight of hyaluronic acid, one of the main constituents of the investigated thixotropic systems, are key determinants of formulation stability. We further showed that changes in both of these parameters reflect on the drug release properties and stiffness of the formulation and could inform subsequent product development based on several use cases. Conclusions: Overall, this study provides an understanding of some key factors that would need to be considered prior to and in the final product development process of thixogels in preparation for commercialization.